Head‐to‐head comparison of prasugrel versus ticagrelor in patients undergoing percutaneous coronary intervention: A meta‐analysis of randomized controlled trials. (13th August 2017) - Sakurai, Ryota; Burazor, Ivana; Bonneau, Heidi N.; Kaneda, Hideaki
Abstract : Objectives: We sought to compare the efficacy and safety of prasugrel and ticagrelor in patients with coronary artery disease undergoing percutaneous coronary intervention (PCI). Background: Evidence from randomized head‐to‐head comparison between prasugrel and ticagrelor is rare regarding clinical endpoints. Methods: PubMed, the Cochrane Library, and Web of Science were queried with the terms "prasugrel, " "ticagrelor, " and "randomized." Relevant randomized controlled trials (RCTs) or the same terms were also surveyed usingclinicaltrials.gov, escardio.org, pcronline.org, andtctmd.com . The clinical endpoints were death, myocardial infarction (MI), stroke, and stent thrombosis (ST) for efficacy, and any bleeding for safety. Results: A total number of 2068 patients in 12 RCTs, whose longest follow‐up period was 6 months, was included in this study. The risks of death (odds ratio [OR]: 0.86, 95% confidence interval [CI]: 0.46‐1.62, P  = 0.647), MI (OR: 1.61, 95%CI: 0.71‐3.62, P  = 0.252), stroke (OR: 1.45, 95%CI: 0.25‐8.36, P  = 0.680), and ST (OR: 0.76, 95%CI: 0.20‐2.81, P  = 0.677) were similar between prasugrel and ticagrelor, respectively. While the incidence of bleeding according to the Bleeding Academic Research Consortium definitions was also comparable (OR: 0.83, 95%CI: 0.45‐1.52, P  = 0.539), that according to the Thrombolysis in Myocardial Infarction criteria was lower in prasugrel than ticagrelor (OR: 0.49, 95%CI: 0.24‐0.97, P  = 0.042). Conclusions: Although the efficacy was similar between prasugrel and ticagrelor, prasugrel may be associated with a lower risk of bleeding compared with ticagrelor during short‐ to mid‐term follow‐up period after PCI. Further studies are warranted in a larger patient population during longer‐term follow up to validate these findings.